A goose-watching visit to northern Iceland - Gillmor, Robert; Blurton Jones, N G (Wildfowl, 1959)
Undue optimism is not wise where bird watching is concerned and perhaps we should have been less disappointed had we treated the assurances that Skagafjordur swarmed with Barnacle Geese in autumn with greater caution. We stayed at Silfrastadir in Skagafjordur (about forty miles south west of the second largest town in Iceland, Akureyri) from 3 to 24 September. We covered the surrounding countryside on foot for an area of about 5 miles in each direction. The fact that we found no sizeable flocks of Barnacle Geese staying in the valley until 13 September was also discouraging. During our stay there were always up to 150 of the local Greylags in the area and these were quite interesting to watch when conditions were suitable.